Complete mitochondrial genome of Cyllorhynchites ursulus (Coleoptera: Rhynchitidae). Issue 2 (3rd July 2018) - Kim, Yung Kun; Lee, Eunok
Abstract: The complete mitochondrial genome of Cylloryhunchites ursulus was sequenced for the first time from its whole body using the next-generation sequencing method. This mitogenome was 14, 508 base pairs in length, containing 13 protein-coding genes, 20 transfer RNA genes, and two ribosomal RNA genes. Its overall A, C, G, and T contents were 37.8, 17.8, 11.1, and 33.4%, respectively. Its A + T content (71.2%) was higher than G + C content. The phylogenetic result showed that although C. ursulus is a species of family Rhynchitidae, its phylogenetic position is closely related to family Attlabidae.